Information and Communication Technology-Based Learning (Pembatik) in 6th State Junior High School of Batauga Subdistrict, South Buton - Jamaluddin, Nur Hidayah Sari; Saprin, Saprin; Rasyid, Muh. Rusydi (Jurnal Mercusuar, 2021)
This research aims to provide a general description of the implementation of ICT-based learning at SMP Negeri 6 Batauga. It is a qualitative case study conducted at SMP Negeri 6 Batauga, located in Batauga sub-district, South Buton district, Southeast Sulawesi province. The research used pedagogical, psychological, and phenomenological approaches. Primary and secondary data sources were used, consisting of the principal, some teachers, and some students. The data collection methods employed were interviews, observations, and documents. Miles and Huberman’s data analysis technique was utilized, involving data collection, data reduction, data presentation, and conclusion drawing. The validity of the data was checked through triangulation techniques. The research results indicate that the implementation of ICT-based learning at SMP Negeri 6 Batauga has only been carried out by three teachers in two years. The implementation of "pembatik" at SMP Negeri 6 Batauga is centered on the computer laboratory or the use of computer hardware, LCD, mobile phones, and laptops. The media used include books, reading texts, images, PowerPoint presentations, and videos. ICT is utilized by students as both a learning medium and source. The implications of this research include the need to improve the school’s facilities such as computers, laptops, LCDs, and wifi networks, to enhance teacher competency, enthusiasm and interest in the urgency of ICT-based learning and to implement it in accordance with the 2013 curriculum in order to optimize ICT-based learning at SMP Negeri 6 Batauga and make it more competitive in this modern era.